Viral infections in Pakistan: prevalence, factors affecting spread, and recommendations for control - Zehra Naseem; Maaha Ayub; Sharaf Ali Shah; Syed Asad Ali; Syed Hani Abidi (Journal of Infection in Developing Countries)
Pakistan is endemic to a number of viral infections, owing to its humid climate, topographical variation, soaring population, and lack of education and awareness. These viruses may have several different modes of transmission, including respiratory or airborne transmission, sexual transmission, blood-borne, fecal-oral transmission, vector-borne transmission, and transmission following an organ transplant. Although several different microorganisms are responsible for causing these infections, a few viruses are found more commonly in Pakistan and are primarily responsible for causing infections. In this study, we present a review of the most recent studies on different viruses, transmitted through various transmission routes, found commonly in Pakistan, along with the prevalence of each, and recommend control measures required against these viruses.